2009
DOI: 10.1111/j.1751-1097.2008.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Structure and Photocycle of PR 2D Crystals with CD and FTIR Spectroscopy

Abstract: We present here a study on proteorhodopsin (PR) 2D crystals with analytical ultracentrifugation, circular dichroism and Fourier transform infrared (FTIR) spectroscopy. The aim of our experiments was to test the activity of 2D crystal sample preparations and to gain further insight in PR structure, stability and function with these techniques. Our results demonstrate higher stability compared to detergent-solubilized or reconstituted samples. For different pH values, low pH 2D crystals tend to form bigger aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Finally the photocycles of solubilized PR in Triton-X 100 and of 2D crystals were found to be almost identical. 25 Our results from the mass spectrum in Fig. 2(a) together with the visual data of the 2D crystals suggest that the photocycle seems to be independent of the oligomeric state.…”
Section: (C) Inset)mentioning
confidence: 55%
“…Finally the photocycles of solubilized PR in Triton-X 100 and of 2D crystals were found to be almost identical. 25 Our results from the mass spectrum in Fig. 2(a) together with the visual data of the 2D crystals suggest that the photocycle seems to be independent of the oligomeric state.…”
Section: (C) Inset)mentioning
confidence: 55%
“…Indeed, it was shown by CD spectroscopy that green PR in 2D crystals shows signals that indicate additional (aromatic) protein−protein contacts, resulting also in higher thermal stability. 58 3D crystal structures of two blue absorbing PRs have been reported. 10 The Med12BPR variant (57% identity to the green PR, PDB ID: 4JQ6) has been crystallized as the hexamer while two mutants of HOT75BPR variant (78% identity, PDB ID: 4KNF, 4JQ6) formed pentamers.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…In order to understand the global ecological implications of PR and to solve the puzzle of its light harvesting and proton translocation, it is very important to resolve its three-dimensional structure. Various methods such as EM and NMR have been used to attempt to solve the structure of PR (Shastri et al, 2007;Liang et al, 2007;Schä fer et al, 2009;Pfleger et al, 2008;Shi et al, 2009), but no three-dimensional structure has been reported to date. To solve the crystal structure of a proteorhodopsin, we attempted to crystallize wild-type blue-lightabsorbing proteorhodopsin (BPR) and green-light-absorbing proteorhodopsin (GPR; Man et al, 2003) and various single and multiple mutants of these and other PRs.…”
Section: Introductionmentioning
confidence: 99%